PENGARUH KAHOOT TERHADAP PENGUASAAN KOSAKATA SISWA KELAS X SMK KANSAI PEKANBARU - Pardede, Lidia Dewi Marlina; Rahayu, Nana; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The research aims to determine the effect of Kahoot in improvingvocabulary mastery in class X students at Kansai Vocational School,Pekanbaru. This research uses a true experimental method. There are two classesselected, namely the experimental class and the control class. The data collectionmethods applied in this research were providing a pretest, carrying out treatment,providing a posttest, and carrying out data analysis techniques. The results of theresearch show that there is an increase in learning outcomes in the experimentalclass using Kahoot. Kahoot media can improve mastery of Japanese vocabularywhen compared to students who were not given treatment with Kahoot. Apartfrom that, students in the experimental class seemed more enthusiastic and active inlearning Japanese. However, in the control class, students who only usedconventional learning methods seemed less enthusiastic while learning Japanese.Keywords: Media, Kahoot, Vocabulary